Functional characterization and clinical significance of IGSF8 in pan-cancer: an integrated bioinformatic and experimental study - Wang, Jie; Lu, Lingxiao; Wu, Ruicheng; Li, Dengxiong; Wang, Zhipeng; Ye, Luxia; Feng, Dechao (Frontiers in Immunology, 2025)
BackgroundImmunoglobulin superfamily member 8 (IGSF8) is a membrane protein implicated in crucial biological processes like cell interactions and immune responses. Emerging evidence suggests that IGSF8 plays a significant role in various cancers by influencing tumor progression through regulation of cell proliferation, migration, and apoptosis. Analyzing its expression, mutation status, and clinical correlations across different cancer types through pan-cancer bioinformatics could provide valuable insights into its potential as a biomarker and target for cancer therapies.MethodsIn this study, we utilized several public databases to investigate the biological role of IGSF8, focusing on its associations with prognosis, tumor heterogeneity, stemness, immune checkpoint genes, and immune cell infiltration across different types of cancer. Additionally, the GDSC and CTRP databases were employed to assess the sensitivity of IGSF8 to small molecule drugs. CCK8 assay and colony formation assay were used to detect its biological effect on cancer cells.ResultsIGSF8 was significantly upregulated in 23 types of cancers and associated with poor prognosis in several cancers, including cell carcinoma and endocervical adenocarcinoma (CESC) and Acute Myeloid Leukemia(LAML). Its high expression was linked to multiple immune regulatory genes and immune checkpoint genes in the tumor microenvironment, with a notable positive correlation with CD276 in most cancers. IGSF8 was also closely associated with multiple indicators of tumor heterogeneity, stemness, as well as significant RNA methylation modifications across various cancers. Drug sensitivity analysis identified BX-795 and tozasertib as potential treatments for tumors with high IGSF8 expression. Knockdown of IGSF8 significantly inhibited the proliferation ability of prostate cancer cells.ConclusionOur findings indicated that IGSF8 might be used as a potential prognostic marker and therapeutic target for various cancers.